Prediction of Quality of Life by Helsinki CT Scoring System in Patients with Traumatic Brain Injury - Shrestha, Bibhusan; Man Karmacharya, Robin; Shalike, Narendra (Nepal Journal of Neuroscience, 2022)
Introduction: Traumatic brain injury (TBI) is an alteration in normally maintained homeostasis and function of the brain owing to any external forces. It is one of the major causes leading to increased disability and morbidity among patients suffering trauma. Hence, we aim to study the association between Helsinki computed tomography CT score on admission to patient’s Quality of Life (QoL) following traumatic brain injury in Dhulikhel Hospital, Nepal. Methods and Materials A prospective observational study was conducted among 44 patients who suffered traumatic brain injury. Eligible patients over 18 years of age diagnosed with traumatic brain injury which is confirmed with a computed tomography scan on admission were included. Outcomes were assessed using the quality of life scale “Project for the Epidemiological Analysis of Critical Care Patients scale (PAEEC)”. Results: Among 44 participants suffering from TBI owing to various modes of injury, male to female ratio was 2.3:1. The mean age among participants was 41.07 years with standard deviation of ± 20.13 (Range 18 – 90 years). Correlation analysis showed that QoL, up to 6 months post-TBI, was significantly associated with Helsinki CT classification. Group 1 and group 2 encompassed subjects who sustained TBI and are in their scheduled 3 monthly and 6 monthly follow up. And significant correlation was noted between two variables r1 = 0.536, p-value = 0.027 and r2 = 0.565, p-value = 0.001 respectively. Conclusion: The present study showed that patients with TBI experience significant quality of life deterioration up to 3-6 months post-TBI. And such deterioration can be predicted by use of Helsinki CT score on admission.